Pengaruh Jenis Pupuk Organik Cair Sebagai Pengganti Media MS Pada Sub Kultur Anggrek Vanda Sp - Ambarsari, Dwi Putri; Asnawati, Asnawati; Listiawati, Agustina (Jurnal Sains Mahasiswa Pertanian, 2019)
Pengaruh Jenis Pupuk Organik Cair Sebagai Pengganti Media MS Pada Sub Kultur Anggrek Vanda Sp Dwi Putri Ambarsari*1, Asnawati2, Agustina Listiawati31Budidaya; Universitas Tanjungpura2Budidaya; Universitas Tanjungpura3Budidaya; Universitas Tanjungpurae-mail: *1dwiputri.dp15@gmail.com ABSTRACTPropagation by in vitro method requires special media, one of them was MS media. MS media in its manufacture requires chemicals that are currently not in cheap price, so need to find a cheaper alternative media but able to produce quality growth materials. The aim of this research is to get the best liquid organic fertilizer (LOF) type as the sub culture medium of orchid Vanda pumila x Vanda 3026. The research was conducted from January 10 to April 10, 2018 at the Biotechnology Laboratory of the Faculty of Agriculture, Tanjungpura University. This study used a Completely Randomized Design (CRD) design with 5 different types of LOF treatment. Each treatment was repeated 5 times, each experimental unit consisting of 4 plant samples. Variables observed is media with LOF types provide the same growth as media MS againts the time shoots form and the number of roots increases. The increase of the number of roots, the number of leaves, time shoots form, the number of shoots. The results of this study showed that the use of MS medium showed better results on the number of shoots and the increase in the number of leaves sub culture of orchids Vanda sp compared various types of LOF media. Keyword: Liqued Organic Fertilizer, Orchid, Sub Culture media, Vanda sp